PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA PEGAWAI YANG DIMEDIASI OLEH BUDAYA ORGANISASI - Pahrul Pahrul; Buyung Sarita; Endro Sukotjo; Nursaban Rommy; Salma Saleh; Hartini Hartini; Juharsah Juharsah (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study is to explain the effect of the style of democratic leadership on organizational citizenship behavior (OCB) and employee performance mediated by organizational culture. The research approach used is the survey method. Data collection is done using instruments in the form of questionnaires. The population of the study was as many as 26 people of the Konawe Kepulauan District Hospital staff except the director (director) because the population was relatively small so that all the population were made respondents. The analytical tool used in hypothesis testing is Partial Least Square (PLS).The results of this study indicate that democratic leadership styles have a significant influence on organizational culture, democratic leadership styles have no significant effect on Organizational Citizenship Behavior, democratic leadership styles have no significant effect on employee performance, organizational culture has a significant effect on Organizational Citizenship Behavior, and organizational culture has a significant effect on employee performance. Thus the organizational culture mediates the influence of democratic leadership styles on Organizational Citizenship Behavior, and employee performance